2023
DOI: 10.5382/econgeo.4976
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Rhyolite Intrusion and Carlin-Type Gold Mineralization at the Cortez Hills Carlin-Type Deposit, Nevada, USA

Abstract: Carlin-type gold deposits (CTDs) of Nevada are the largest producers of gold in the United States, a leader in world gold production. Although much has been resolved about the characteristics and origin of CTDs in Nevada, major questions remain, especially about (1) the role of magmatism, whether only a source of heat or also metals, (2) whether CTDs only formed in the Eocene, and (3) whether pre-Eocene metal concentrations contributed to Eocene deposits. These issues are exemplified by the CTDs of the Cortez … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 134 publications
0
1
0
Order By: Relevance
“…The Carlin-type gold deposits (CTDs), one of the most significant hydrothermal gold deposits, have attracted considerable attention due to their extensive metallogenic scale and promising exploration potential [1,2]. In recent years, many studies have revealed that some geological and geochemical characteristics of these gold deposits in China differ from those of the most typical Carlin-type gold deposits in Nevada, USA.…”
Section: Introductionmentioning
confidence: 99%
“…The Carlin-type gold deposits (CTDs), one of the most significant hydrothermal gold deposits, have attracted considerable attention due to their extensive metallogenic scale and promising exploration potential [1,2]. In recent years, many studies have revealed that some geological and geochemical characteristics of these gold deposits in China differ from those of the most typical Carlin-type gold deposits in Nevada, USA.…”
Section: Introductionmentioning
confidence: 99%